12. Q12a
Save videos to My Cheatsheet for later, for easy studying.
Video Solution
Q1
Q2
Q3
L1
L2
L3
Similar Question 1
<p> Simplify each system, and then solve it by substitution. Check each solution.</p><p><code class='latex inline'>\displaystyle 2(x-1)-4(2 y+1)=-1\\x+3(3 y+2)=2 </code></p>
Similar Question 2
<p>Simplify the equation, and then solve the linear system by substitution. Round your answers to the nearest tenth, if necessary.</p><p><code class='latex inline'>3(x-1)-(y+1)=1</code></p><p><code class='latex inline'>4(x+1) + 2(y-1) = 10</code></p>
Similar Question 3
<p> Solve for <code class='latex inline'>x</code> and <code class='latex inline'>y</code> using the substitution method for each linear system.</p> <ul> <li><code class='latex inline'>\displaystyle x - y = 2x + 3</code></li> <li> <code class='latex inline'>x - 3y = 5 - 5y</code></li> </ul>
Similar Questions
Learning Path
L1 Quick Intro to Factoring Trinomial with Leading a
L2 Introduction to Factoring ax^2+bx+c
L3 Factoring ax^2+bx+c, ex1
Now You Try
<p>Simplify each equation, and then solve the linear system by substitution.</p><p><code class='latex inline'> \displaystyle \begin{array}{cccc} &2(x - 4) + y = 6 \\ &3x - 2(y -3) = 13 \end{array} </code></p>
<p> Solve for <code class='latex inline'>x</code> and <code class='latex inline'>y</code> using the substitution method for each linear system.</p> <ul> <li><code class='latex inline'>\displaystyle x - y = 2x + 3</code></li> <li> <code class='latex inline'>x - 3y = 5 - 5y</code></li> </ul>
<p>Simplify the equation, and then solve the linear system by substitution. Round your answers to the nearest tenth, if necessary.</p><p><code class='latex inline'>\displaystyle \begin{array}{llllllll} 2(x+ 1)+3(y + 2) = 15\\ x + 3(y - 1) = 2 \end{array} </code></p>
<p> Simplify each system, and then solve it by substitution. Check each solution.</p><p><code class='latex inline'>\displaystyle 2(3 x-1)-(y+4)=-7\\4(1-2 x)-3(3-y)=-12 </code></p>
<p>Solve the linear system.</p><p><code class='latex inline'> \displaystyle \begin{array}{llll} &2(2x -1) - (y - 4) =11 \\ &3(1 - x) - 2(y - 3) =-7 \\ \end{array} </code></p>
<p>Simplify the equation, and then solve the linear system by substitution. Round your answers to the nearest tenth, if necessary.</p><p><code class='latex inline'> 2(x+1) +3(y+2) = 10</code></p><p><code class='latex inline'> -(x+3) + 2(y-1) = 1</code></p>
<p>Solve each linear system with your choice of method.</p><p><code class='latex inline'> \displaystyle 2(x - 1) -3 (y - 3) = 0 </code> and </p><p><code class='latex inline'> \displaystyle 3(x + 2) -(y - 7) = 20 </code></p>
<p>Simplify and then solve each linear system.</p><p><code class='latex inline'>\displaystyle \begin{array}{lllll} & 3(x + 1)-4(y -1) =13 \\ & 5(x + 2)+2(y +3) =0 \end{array} </code></p>
<p>Simplify each equation, and then solve the linear system by substitution.</p><p><code class='latex inline'> \displaystyle \begin{array}{cccc} &2(x - 1) - 4(2y +1) = -1 \\ &x + 3(3y + 2) -2 = 0 \end{array} </code></p>
<p>Simplify the equation, and then solve the linear system by substitution. Round your answers to the nearest tenth, if necessary.</p><p><code class='latex inline'> 2(x-1) + y =5</code></p><p><code class='latex inline'>4x-3(y+2) = 15</code></p>
<p> Simplify each system, and then solve it by substitution. Check each solution.</p><p><code class='latex inline'>\displaystyle 2(x-1)-3(y-3)=0\\3(x+2)-(y-7)=20 </code></p>
<p>Simplify the equation, and then solve the linear system by substitution. Round your answers to the nearest tenth, if necessary.</p><p><code class='latex inline'>3(x-1)-(y+1)=1</code></p><p><code class='latex inline'>4(x+1) + 2(y-1) = 10</code></p>
<p>Simplify each system, and then solve it by substitution. Check each solution.</p><p><code class='latex inline'>\displaystyle 2(x-4)+y=6 </code></p><p><code class='latex inline'>\displaystyle 3 x-2(y-3)=13 </code></p>
<p>Expand and simplify each equation. Then, solve the linear system.</p><p><code class='latex inline'> \displaystyle \begin{cases} 2(3x - 1) - (y + 4) = -7\\ 4(1 - 2x) - 3(3 - y) = -12 \end{cases} </code></p>
<p> Simplify each system, and then solve it by substitution. Check each solution.</p><p><code class='latex inline'>\displaystyle 2(x-1)-4(2 y+1)=-1\\x+3(3 y+2)=2 </code></p>
How did you do?
Found an error or missing video? We'll update it within the hour! ðŸ‘‰
Save videos to My Cheatsheet for later, for easy studying.